Social Anxiety Disparity Between Extroverted and Introverted Psychology Students During COVID-19 at University "X" - Sigarlaki, Miryam Ariadne Sigarlaki; Setiawati, Lilis Saputri (Journal of Health and Behavioral Science, 2023)
Social anxiety is a global phenomenon that can be experienced by various groups, one of which is students with extroverted and introverted personality types. The purpose of this research is to determine the difference in the level of social anxiety between extroverted and introverted personality types among students during the COVID-19 pandemic. This study is a comparative quantitative study that uses proportionate stratified random sampling with a sample size of 139. The measurement tools used are the Eysenck Personality Inventory to measure personality types and the Liebowitz Social Anxiety Scale to measure social anxiety. Hypothesis testing shows that there is a significant difference in the level of social anxiety between extroverted and introverted personality types. Introverted personality types have a higher level of social anxiety compared to extroverted personality types. This significant difference is due to the differing characteristics of extroverted and introverted personality types in facing social situations, resulting in different tendencies towards social anxiety, whereas introverts tend to have higher social anxiety tendencies.